Gamma-ray, stable carbon and oxygen isotope chemostratigraphy and sequence stratigraphy of the Lower Mahil Formation (KS-1 Khuff-Equivalent), Northern Oman - Moustafa, Mohamed S. H.; Al Raqaishi, Rasha; El-Ghali, Mohamed A. K.; Gharbi, Mohamed; Abbasi, Iftikhar Ahmed; Al Humaidi, Aaraf; Al Ghafri, Nada; Alshukaili, Marwa Musallam; Al-Awah, Hezam (Frontiers in Earth Science, 2023)
This research presents findings from a study on the Lower Triassic (Induan) Lower Mahil 19 KS-1 Formation on a shallow carbonate platform in Northern Oman. The KS-1 Formation exhibits 20 distinctive sequence stratigraphy marked by notable thickness variations, slumps, and breccia de-21 posits formed due to the activity of active normal faults alongside intra-basin growth faults. The 22 main objective was to establish a reliable stratigraphic framework for the Lower Mahil KS-1 For-23 mation by integrating high-resolution carbon isotope data and high-resolution spectral and total 24 gamma-ray data. To achieve this, whole-rock samples were analyzed for δ 13 C and δ 18 O isotopes. 25 Spectral and total gamma-ray records were obtained for the formation. Isotope sampling is con-26 ducted every 0.5 meters in the Saiq Plateau and Wadi Sahtan sections. Furthermore, spectral 27 gamma-ray measurements were taken at intervals of 10 cm from the logged sections. Within the 28 third-order sequence, the spectral gamma-ray data revealed a distinct sea-level trend, leading to the 29 division of KS1 into two parts. Five fourth-order depositional sequences were identified by analyz-30 ing stable carbon isotopes, uranium, and total gamma-ray profiles. Four of these sequences dis-31 played complete patterns, reflecting transgression and regression phases, while the fifth sequence 32 was incomplete and solely comprised a transgressive phase.An essential outcome of the study is the correlation of the δ 13 C curve of the Lower Mahil KS-1 For-34 mation with other similar formations around the Tethys region. This correlation indicates that the 35 Lower Mahil KS-1 Formation captures the near-primary signal of carbon isotope variations in coeval 36 seawater. As a result, it holds promise as a reference section for future investigations and studies in 37 this field. Compared to the prior investigation, this study utilizes data with higher precision, cap-38 turing spectral gamma-ray measurements at 10-cm intervals and isotope measurements at 50 cm 39 intervals. Furthermore, the study's focus is confined explicitly to KS1.